2016
DOI: 10.5897/ajb2016.15368
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from date palm fruit waste fermentation using solar energy

Abstract: Every year, more than 236,807 tons, equivalent to 30% of date-palm fruits produced in Algeria, is lost during picking, storage, and commercialization processes. Gasification of this huge biomass can generate biogas such as bioethanol, biodiesel, gasoline and other useful substances. Bioethanol is becoming the main biofuel produced by chemical synthesis or anaerobic fermentation from biomass and is significant for industrial development, investment, and use. It is eco-friendly, moderately costly and cleaner tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The yield of alcohol from spoilage date fruits fermentation medium was greater as compared to synthetic medium containing the same sugar concentration (Abd-Alla & El-Enany, 2012). Our results are also similar to the results of Boulal et al (2016) and Mehani et al (2013) who have reported the fermentation time of sugars from 36 to 72 hr.…”
Section: Effect Of Sugars On Ethanol Productionsupporting
confidence: 93%
See 3 more Smart Citations
“…The yield of alcohol from spoilage date fruits fermentation medium was greater as compared to synthetic medium containing the same sugar concentration (Abd-Alla & El-Enany, 2012). Our results are also similar to the results of Boulal et al (2016) and Mehani et al (2013) who have reported the fermentation time of sugars from 36 to 72 hr.…”
Section: Effect Of Sugars On Ethanol Productionsupporting
confidence: 93%
“…The infrared spectra analysis also identified the vibration signs of biofuel from the waste date palm. The results revealed that wave numbers 2,900 and 3,300 cm −1 link to CH and OH molecule groups, respectively (Boulal et al, 2016;Manzoor et al, 2019Manzoor et al, , 2020Mehani et al, 2013).…”
Section: Fourier Transformer Infrared Spectroscopy Analysis Of Ethanolmentioning
confidence: 94%
See 2 more Smart Citations
“…The concentration of the ethanol in the alcohol produced (Figure 8) is performed using liquid chromatography (Benziouches, 2011). After distillation of the date juice, a significant specific production of the bioethanol reached 180, and 200.5 mL/kg of dates at 90°C was obtained, representing bioconversion efficiencies of 23.57 and 26.2% for both variety of dates (T & L) respectively (Ahmed et al, 2016). Finally, the vibration sign of the biofuel produced ( Figure 9) is identified using Infra-Red Spectra.…”
Section: Resultsmentioning
confidence: 99%